Design and Evaluation of ACAFiB-APP, a clinical decision support system for anticoagulant considerations in patients with atrial fibrillation - Ramin Ansari; Sorayya Rezayi; Ali Asghar Safaei; Reza Mollazadeh; Eisa Rezaei; Mahboobeh Khabaz Mafinejad; Soha Namazi; Keyhan Mohammadi (BMC Cardiovascular Disorders)
Abstract Background Patients with atrial fibrillation are at risk for various complications, including thromboembolic events. This study involves developing and evaluating a Clinical Decision Support System (CDSS) to select appropriate anticoagulant drug, considering comorbidities, laboratory data, and concurrent medications. The system is based on a streamlined interpretation of the most recent globally accepted clinical guidelines. Methods Primarily a semi-structured interview regarding the challenges in the field of thromboprophylaxis for AF and clinical pharmacists and cardiologists’ needs in practice was conducted. Then the required data were extracted from the latest guidelines and confirmed by the expert panel. Using Microsoft Visio software each scenario and its corresponding rules were modeled. Dart programming language, the Flutter framework, and the Visual Studio editor were used to develop the application. Finally, the uMARS questionnaire was used to evaluate the application quality. Results The selection of the anticoagulants was reported to be the most challenging domain by 78.6% of the participants in the interview. According to the designed algorithms, the application was developed using Asp.net with the Microsoft SQL Server database platform. This CDSS is called ACAFiB-APP, which stands for Anticoagulant in AF Application. The user goes through various calculators and obtains the required data, moreover, the user will choose one or more comorbidities/clinical scenarios. Finally, ACAFiB-APP will represent the proper anticoagulant options with dosing and related considerations. All of the sections in the uMARS questionnaire received acceptable scores. Conclusions The CDSS will facilitate the informed selection of anticoagulants for complicated AF cases by considering the patient clinical scenario. Clinical trial number Not applicable.